Overview of Plasma and Platelet Transfusions in Critically Ill Children - Kahn, Stacie; Chegondi, Madhuradhar; Nellis, Marianne E.; Karam, Oliver (Frontiers in Pediatrics, 2020)
Critically ill children are a unique population who frequently receive plasma and platelet transfusions for both active bleeding or mitigation of bleeding risk. While these products are frequently administered, transfusion indications in this population remain unclear and practice varies across institutions and providers. In this manuscript we will outline the current evidence regarding plasma and platelet transfusions for hemostasis in the pediatric intensive care setting. For both products, we will describe the product composition, epidemiology, product indications, and discuss the potential risks and benefits involved with the transfusion. We will also discuss knowledge gaps and future areas of research.